RUPTURA NA ESCOLA INFANTIL: ASPECTOS FORMAIS, GEOMÉTRICOS E TOPOLÓGICOS APLICADOS AO ESPAÇO CONSTRUÍDO - Rambo, Mirian Hossa; Medeiros, Valério Augusto Soares de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The conception of contemporary children´s school is subject to technical requirements and pedagogical recommendations, which guide the architectural design process. Both the arrangement and relation between spaces are inherent to these conditioning factors and design guidelines, however, they are presented implicitly and rather elementarily. Therefore, the research aims to explore the dynamics of design, appropriation and intervention in the built space. The Proinfancia Program Standard Project and its revisions are the case study. The experiences of the users and the school's spatial configuration integrates the reserarch. Three questions conduct the reading: (1) In what ways do the school users intervene in the constructed space with respect to the Geometric and Functional Aspects? (2) To what extent do these interventions relate to the Topological Aspects? (3) In what ways does the sequence project-execution-revisions, from the perspective of Proinfancia Program schools, succeed in producing children's school spaces? The obtained results reveal that changes in use, occupation and physical attributes of the spaces reflect the inadequacy of the school planning in connection to the expectations and demands of the end-user and that they correlate with the configurational and topological potentials of the architectural model developed.